Variation among individual dairy cows in methane measurements made on farm during milking - Garnsworthy, P.C.; Craigon, J.; Hernandez-Medrano, J.H.; Saunders, N. (American Dairy Science Association, 2012)
The objective of this study was to quantify on-farm variation between and within cows in methane emissions measured during milking, and to determine which factors are related to this variation. Methane emission rate during milking (MERm) was recorded at milking using methane analyzers installed in automatic (robotic) milking stations for 215 cows over a period of 5mo. Between-cow variation in MERm (mean 2.07, SD 0.629g/min), was greater than within-cow variation and was related to variation in body weight, milk yield, parity, and week of lactation. Estimation of daily methane emissions from MERm data, using an equation derived from comparisons with respiration chamber data, produced estimates that ranged from 278 to 456g of CH4/d and were commensurate with values predicted from metabolizable energy requirements for observed body weight and milk yield. It is concluded that methane emissions vary considerably between dairy cows housed under commercial conditions. This variation needs to be taken into account when performing inventories or testing mitigation strategies, but it might offer opportunities for genetic selection.